Predictive factors suggesting an underestimation of gastric lesions initially diagnosed as adenomas by forceps biopsy - Ko, Sung Jun; Yang, Min A; Yun, So Hee; Park, Moon Sik; Han, Shang Hoon; Cho, Jin Woong (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: The endoscopic forceps biopsy of gastric lesion may provide inadequate specimens for a correct diagnosis of the entire lesion. Therefore, a histologic discrepancy may exist between specimens obtained by forceps biopsy and by endoscopic resection. The aim of this study was to evaluate the endoscopic characteristics of an underestimation in gastric carcinomas initially diagnosed as adenomas by forceps biopsy. Materials and Methods: We retrospectively reviewed 431 lesions diagnosed as gastric adenomas by forceps biopsy and resected by endoscopic submucosal dissection (ESD) between January 2008 and December 2011. The endoscopic findings were reviewed for location, size, gross appearance, ulceration, and surface color. We compared these variables between the adenoma group and the carcinoma group, as defined by the post-resection pathological findings. Results: The mean patient age was 65.63±9.30 years in the adenoma group and 64.75±10.30 years in the carcinoma group. The mean size of the lesion was 21.04±8.65 mm in the adenoma group and 22.06±7.46 mm in the carcinoma group. In the multivariate analysis, high-grade dysplasia from endoscopic forceps biopsy and red discoloration were significant variables associated with carcinoma in post-resection histology. Conclusion: Gastric adenomatous lesions with endoscopic characteristics of surface redness and high-grade dysplasia on forceps biopsy should be resected completely by ESD because of the high possibility of an underestimation after ESD.